Electroplating and functional properties of Fe-Mo and Fe-Mo-W coatings - Ved, M. V.; Sakhnenko, N. D.; Karakurkchi, A. V.; Yermolenko, I. Yu. (Украинский государственный химико-технологический университет, 2014)
Peculiarities of electrodeposition Fe-Mo and Fe-Mo-W coatings from citrate bath containing iron (III) on substrates of mild steel and cast iron are investigated. The utilization of iron (III) compounds significantly enhanced the stability and service life of electrolyte due to elimination redox reactions involving complexing and side anodic reactions. The effect of alloying components salt concentration and electrolysis mode on the quality, composition and properties of the alloys were determined. It is shown that alloys formed in nonstationary electrolysis have a uniform surface, composition and a lower content of impurities. Increased physical and mechanical properties as well as corrosion resistance of Fe-Mo and Fe-Mo-W coatings compared with the base metal are caused by the presence of propensity for passivation alloying components as well as by amorphous structure of electroplating alloys. Indicated coatings can be considered as promising in surface hardening technologies and repair of of worn items.

Исследованы особенности электрохимического формирования покрытий Fe-Mo и Fe-Mo-W из цитратного электролита на основе железа (III) на подложках из малоуглеродистой стали и серого чугуна. Применение соединений железа (III) позволило существенно повысить стабильность и ресурс электролита за счет исключения редокс реакций с участием комплексообразователей и нецелевых анодных реакций. Установлено влияние концентрации солей сплавообразующих компонентов и режимов электролиза на качество, состав и свойства полученных сплавов. Показано, что сплавы, сформированные в условиях нестационарного электролиза, имеют более равномерную поверхность и состав, характеризуются меньшим содержанием примесей. Повышенные, в сравнении с основным металлом, физико-механические и антикоррозионные показатели покрытий Fe-Mo и Fe-Mo-W обусловлены как наличием склонных к пассивации легирующих компонентов, так и аморфной структурой сплавов. Полученные покрытия можно рассматривать как перспективные в технологиях упрочнения поверхностей и ремонта изношенных изделий.
Гальванические и функциональные свойства покрытий Fe-Mo и Fe-Mo-W
Keywords: citrate bath; physic-mechanical properties; electrodeposition; corrosion resistance; nonstationary electrolysis; электролит цитратный; свойства физико-механические; электроосаждение; стойкость коррозионная; электролиз нестационарный